Effects of Leishmania major infection on the gut microbiome of resistant and susceptible mice - Mrázek, Jakub; Mrázková, Lucie; Mekadim, Chahrazed; Jarošíková, Taťána; Krayem, Imtissal; Sohrabi, Yahya; Demant, Peter; Lipoldová, Marie (Applied microbiology and biotechnology, 2024)
Cutaneous leishmaniasis, a parasitic disease caused by Leishmania major, is a widely frequent form in humans. To explore the importance of the host gut microbiota and to investigate its changes during L. major infection, two different groups of mouse models were assessed. The microbiome of two parts of the host gut-ileum and colon-from infected and non-infected mice were characterised by sequencing of 16S rDNA using an Ion Torrent PGM platform. Microbiome analysis was performed to reveal changes related to the susceptibility and the genetics of mice strains in two different gut compartments and to compare the results between infected and non-infected mice. The results showed that Leishmania infection affects mainly the ileum microbiota, whereas the colon bacterial community was more stable. Different biomarkers were determined in the gut microbiota of infected resistant mice and infected susceptible mice using LEfSe analysis. Lactobacillaceae was associated with resistance in the colon microbiota of all resistant mice strains infected with L. major. Genes related to xenobiotic biodegradation and metabolism and amino acid metabolism were primarily enriched in the small intestine microbiome of resistant strains, while genes associated with carbohydrate metabolism and glycan biosynthesis and metabolism were most abundant in the gut microbiome of the infected susceptible mice. These results should improve our understanding of host-parasite interaction and provide important insights into the effect of leishmaniasis on the gut microbiota. Also, this study highlights the role of host genetic variation in shaping the diversity and composition of the gut microbiome. KEY POINTS: • Leishmaniasis may affect mainly the ileum microbiota while colon microbiota was more stable. • Biomarkers related with resistance or susceptibility were determined in the gut microbiota of mice. • Several pathways were predicted to be upregulated in the gut microbiota of resistant or susceptible mice.
Keywords: Gastrointestinal Microbiome; Microbiome analysis; Humans; Leishmania major; Mouse models; leishmanióza kožní; Host-parasite interaction; lidé; Biomarkers; zvířata; myši; Disease Susceptibility; náchylnost k nemoci; Mice; Leishmaniasis, Cutaneous; biologické markery; Gut microbiota; Cutaneous leishmaniasis; střevní mikroflóra; Animals; Leishmania major infection